Internet of things (IOT) for smart solar energy: A case study of the smart farm at Maejo University - Oran Chieochan (2018)
© 2017 IEEE. This research aims to prototype a small smart off-grid solar cell system. o provide an alternative electrical supply for a smart Lingzhi mushroom farm. This research applied the use of IOT with voltage and current sensors to measure and monitor the voltage of solar cell charging, amp (ampere) of current charging from the solar panel into a battery and (ampere) of current loading from a battery to the irrigation systems (fog and sprinkler pumps). Voltage and current data processed through Blynk was developed as an IOT cloud service. Data was stored into the Blynk and displayed on mobile devices in real time. The functional status (switching on and off for periods of time, current consumption) pushes notifications through Blynk IOT cloud service on the Blynk application. The equipment and tools used in this research were NodeMCU, voltage and current sensors, relay modules, DC sprinkler, and fog pumps. A small off-grid solar cell was applied. The solar cell system consists of a charger, battery, and solar panels. The IOT cloud used is Blynk. The results of the research shows that using IOT with voltage and current sensors enhances the prototype of a smart farming as an alternative and green electrical resource.